(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This paper explores concept, significance, and key aspects of the “Ungujol” doctrine. It highlights the values of the Kyrgyz people, the current state is analyzed, alohg with the importance of properly guiding the younger generation and the essential role of science and education.